Cerebrovascular disease: introduction and perspective - Hachinski, Vladimir (Henry Stewart Talks, 2008)
The growing burden of stroke, Silent strokes, subtle thieves of mind, A comprehensive approach to prevention, A prioritized approach to stroke, Keeping up without staying up